Can someone please explain to me how r(t)=(1-t)<1,3,-2>+t<2,-1,3> became r(t)=<1+t,3-4t,-2+5t>

Can someone please explain to me how r(t)=(1-t)<1,3,-2>+t<2,-1,3> became r(t)=<1+t,3-4t,-2+5t>

See more answers at brainly.com

@Azteck can you lease help?!

what are the these "<" signs doing there?

theyre supposed to represent vectors

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.